Three-dimensional Winston–Lutz test using reusable polyvinyl alcohol-iodide (PVA-I) radiochromic gel dosimeter. (1st October 2021) - Ono, Kaoru; Fujino, Keisuke; Kurihara, Ryosuke; Hayashi, Shin-ichiro; Akagi, Yukio; Hirokawa, Yutaka
Abstract: Medical linear-accelerator-based stereotactic radiosurgery (SRS) using a stereotactic apparatus or image-guided radiotherapy system for intracranial lesions is performed widely in clinical practice. In general, Winston–Lutz (WL) tests using films or electric portal imaging devices (EPIDs) have been performed as pre-treatment and routine quality assurance (QA) for the abovementioned treatment. Two-dimensional displacements between the radiation isocentre and mechanical isocentre are analysed from the test; therefore, it is difficult to identify the three-dimensional (3D) isocentre position intuitively. In this study, we developed an innovative 3D WL test for SRS-QA using a novel radiochromic gel dosimeter based on a polyvinyl alcohol-iodide (PVA-I) complex that can be reused after annealing. A WL gel phantom that was consisted of the PVA-I gel dosimeter poured into a tall acrylic container and an embedded small tungsten sphere was used as a position detector. A flatbed scanner was used to analyse the isocentre position. The measured 3D isocentre accuracy from the gel-based WL test was within 0.1 mm compared with that obtained from the EPID-based WL test. Furthermore, excellent reusability of the WL gel phantom was observed in long-term SRS isocentre verification, in which clinical SRS cases involving repeated irradiation and annealing were analysed. These results demonstrate the high accuracy and reliable evaluation of the isocentre position using an innovative test. In addition, the clinical-based routine SRS-QA using the PVA-I gel dosimeter demonstrates a highly convenience while affording an easy and fast analysis process.